Analisis Maqashid Al-Syariah Dalam Sistem Ekonomi Islam dan Pancasila - Ubbadul Adzkiya (Universitas Alma Ata, 2020)
The development of the Islamic economy in Indonesia has made the significant progress. Islamic economics has the spirit to integrate between the economy with religious theology. Indonesia has claimed itself as a country based on Pancasila and Constitution of 1945. Among Muslim economists, there are various opinions on the relationship between the state and religion that related to the position of the Islamic economy in a framework of the Indonesian State.This paper aims to strengthen the Islamic economic system in Indonesia, to strengthen Pancasila is according to maqashid al-sharia in economic terms, and a relevant alternative relationship between Islamic economy and Pancasila. The results of this study are The Islamic economy system in Indonesia is done in line with Pancasila as the basis of the State. This is based on the idea that Pancasila has included the interests of Muslims that are relevant with the objectives of sharia (maqashid al-syariah).